PERENCANAAN KEUANGAN PENDIDIKAN ISLAM - Nabhaan, Fadhiil; Ardiansyah, Anas; Mujahidin, Endin (Journal of Research and Publication Innovation, 2024)
Different systems, education needs material as a driving force like the economy in running a society, at least at least to revive the human resources involved in the institution. This article aims to look at the financial planning of Islamic education theoretically and what happens in the field. The method used in this research is library research and qualitative field data, financial management and financing of educational institutions can be interpreted as a series of activities to manage the finances of educational institutions ranging from planning, extracting cost resources, bookkeeping, spending, supervision and accountability and financial reporting of educational institutions so that the organisation or educational institution runs effectively and efficiently in carrying out the function of providing high-quality educational services. Even in Islam the Qur'an instructs us to be familiar with administrative activities and Bookkeeping.